Knowledge and self management practice regarding diabetes among diabetic patients in Bhaktapur municipality, Bhaktapur district, Nepal. - Shrestha,Manisha (2019)
ABSTRACT: Introduction: Diabetes is considered as a major type of non communicable disease and is a public health problem and is a sixth leading cause of mortality in the world. Self management practice is a number of choices that the patients with diabetes must take care. Diabetes is categorized into two types that are type I diabetes and type II diabetes. The prevalence of diabetes in 20 years and above are 14.6% in urban and 2.5% in rural area. Objectives: To assess the knowledge and self-management practice regarding diabetes among diabetic patients in Bhaktapur municipality, Bhaktapur, Nepal. Methodology: Descriptive cross sectional study was adopted to study the knowledge and self care management practice among diabetic patients. The study population was 245 and the study period was from Baisakh 2075 to Baisakh 2076 in Bhaktapur Municipality. Findings: The study was carried out in 245 respondents among them the only (4.5 %) of respondent have adequate knowledge and majority of respondents (95.5%) have inadequate knowledge. In these respondents practice seem to be sufficient. Among the respondent, majority of the respondents (87.3%) have inadequate practice and (12.7%) have adequate management practice. Most of the respondents (84.1%) have positive thinking and only (15.9%) have negative thinking towards diabetes. On diabetes Knowledge and in these respondents practice seems to be inadequate. Conclusion: the study concluded that there is poor knowledge, positive thinking but inadequate practice of diabetes among diabetic patients in Bhaktapur municipality.